2013
DOI: 10.22610/jebs.v5i11.454
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Frame Dependence on Investment Decisions made by Listed Property Fund Managers in South Africa

Abstract: Behavioural finance describes investors' and managers'behaviour in terms of their interactions, andhow their behaviour subsequently influences financial and capital markets. One aspect of behavioural finance, frame dependence, reflects the fact that decision-makers may model decisions about problems using subjective frames. Such decisions may lead to errors in judgement. This study's objective was to determine whether frame dependence influences listed property fund managers in South Africa's property investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Using multiple regression to analyze data obtained from property loan stock companies in South Africa, the findings revealed that the information provided by the listed companies are insufficient and of limited use for property investment decision making. Based on the analysis of the real estate investment decision-making process of listed property managers in South Africa, Lowies et al (2013) submitted that biases and human judgment such as heuristics and frame dependence propelled by human cognitive reasoning introduce behavioral bias into the real estate allocation process. This influences the asset allocation decision-making practice and impairs it from conforming to the normative model.…”
Section: Institutionalmentioning
confidence: 99%
“…Using multiple regression to analyze data obtained from property loan stock companies in South Africa, the findings revealed that the information provided by the listed companies are insufficient and of limited use for property investment decision making. Based on the analysis of the real estate investment decision-making process of listed property managers in South Africa, Lowies et al (2013) submitted that biases and human judgment such as heuristics and frame dependence propelled by human cognitive reasoning introduce behavioral bias into the real estate allocation process. This influences the asset allocation decision-making practice and impairs it from conforming to the normative model.…”
Section: Institutionalmentioning
confidence: 99%
“…Country-specific studiesfor example, India (Tripathi and Chattopadhyay, 2013), Pakistan (Mahmood et al, 2016), Kenya (Arthur. 2014), Tunisia (Boussaidi, 2013) Sri Lanka (Kengatharan, 2014), and South Africa (Lowies et al, 2013) were conducted in many jurisdictions as part of academic support to capital market development in various countries. Hence, the key contribution to the literature in this paper is the attempt to fill the gap in the dearth of information on identifying the empirical behavioural factors influencing investment decisions in Oman, with emphasis on the emerging scenario in the country's capital market.…”
Section: Contribution To Knowledgementioning
confidence: 99%
“…The empirical evidences are inadequate to identify the linkage between the economic growth and the development of the stock market. There is a positive correlation between real economic growth particularly in the developing countries and the stock market activities (Lowies et al, 2013;Chodorow-Reich et al, 2019). The management approach in the selection of an optimum portfolio remain critical issue for investors, analysts, and academicians.…”
Section: The Continuing Search For Real Evidence Of the Linkage Betwementioning
confidence: 99%
See 1 more Smart Citation
“…While there is substantial and growing research on the 'science' aspect of the methodological model, covering the systematic selection and mathematical analysis of comparables and parameters in ensuring property valuation validity, the descriptive 'art' behavioural property valuation uncertainty is often neglected, particularly on how property Valuers' subjective decision-making process contributes to the inaccuracy and uncertainty of valuation. Studies by Klamer et al, (2017), Kucharska-Stasiak (2013), Lowies et al, (2013), Whittle et al, (2014), Iroham et al, (2014) and Warren-Myers (2015) acknowledge this gap, and they recommend further research into the need of behavioural uncertainties of Valuers in property valuation.…”
Section: Introductionmentioning
confidence: 99%